Evaluate the expression.
Drag the answer into the box to match the expression.

[tex]27.((3^{3})^{-1} = 27.(27)^{-1} = 27 .\frac{1}{27} = 1[/tex]
This is because [tex]3^{3} = 3 x 3 x 3 = 9 x 3 = 27[/tex]
And [tex](27)^{-1} means \frac{1}{27}[/tex]
For this reason, [tex]27. (27)^{-1} = 1[/tex]
Positive indices mean we have to multiply the same number twice or thrice based on the value of the index. On the other hand, negative indices mean we have to divide by the same number twice or thrice based on the value of the index.
Answer:
27.((3^{3})^{-1} = 27.(27)^{-1} = 27 .\frac{1}{27} = 1
Step-by-step explanation: